Clinical spectrum of congenital heart diseases in a tertiary care hospital - Sharja Phuljhele; Shashikant Dewangan; Pranali Thombre (International Journal of Medical Research and Review, 2016)
Introduction- In developing countries congenital heart diseases (CHDs) causes deaths of thousands of children. A study is necessary to understand incidence and clinical spectrum of CHDs so that early diagnosis and intervention can be done.Material and Methods – Newborns and children up to the age of 14 years attending pediatric OPD as well as admitted in ward with CHDs enrolled for study. Data were analyzed using SPSS system version 21.Results- A total of 400 children with CHDs included for final analysis. Male to Female ratio is 1.78:1.Most common CHDs was Ventricular septal defect followed by Tetralogy of fallot. Major symptoms were cough, difficulty in breathing, poor weight gain and suck rest suck cycle. Maternal risk factors found were consanguinity, maternal diabetes mellitus, maternal hypertension, maternal seizure disorder, maternal obesity, systematic lupus erythematosus etc.Conclusion- VSD is most common acyanotic CHD. Males are more affected with CHDs. Consanguinity and Maternal Diabetes are important risk factors for CHDs.